1961
DOI: 10.1136/gut.2.1.18
|View full text |Cite
|
Sign up to set email alerts
|

A study of malabsorption after resection of the entire jejunum and the proximal half of the ileum

Abstract: SYNOPSIS Biochemical, haematological, and radiological investigations are reported in a young child in whom nearly 80% of the small intestine was resected. The prognosis in a child after such extensive resection is probably better than in an adult, as natural growth can still occur with the expectation of greater adaptability as well as of increased length of the remaining segments.The supreme role of the small intestine in digestion and absorption makes it an indispensable organ. Elaboration of the functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1962
1962
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Reports of 12 patients with documented steatorrhoea followed for at least one year and up to seven years after resection failed to reveal any neuropathy; tetany, however, was not uncommon (Anderson, 1965;Opie, Hunt, and Finlay, 1964;Booth, MacIntyre, and Mollin, 1964;Clayton and Cotton, 1961;Todd, Dittebrandt, Montague, and West, 1940;Berman, Ulevitch, Haft, and Lemish, 1950;Bothe, Magee, and Driscoll, 1954;Trafford, 1956;Linder, Jackson, and Linder, 1953). Eight other patients with massive resections showed no neurological abnormalities (Althausen, Doig, Uyeyama, and Weiden, 1950;Berman, Habegger, and Billings, 1953;Fletcher, Henley, Sammons, and Squire, 1960;Holman, 1944;Martin, Robertson, and Dennis, 1948;Mayer and Criep, 1949;Pincus, 1951).…”
Section: Case Reportsmentioning
confidence: 99%
“…Reports of 12 patients with documented steatorrhoea followed for at least one year and up to seven years after resection failed to reveal any neuropathy; tetany, however, was not uncommon (Anderson, 1965;Opie, Hunt, and Finlay, 1964;Booth, MacIntyre, and Mollin, 1964;Clayton and Cotton, 1961;Todd, Dittebrandt, Montague, and West, 1940;Berman, Ulevitch, Haft, and Lemish, 1950;Bothe, Magee, and Driscoll, 1954;Trafford, 1956;Linder, Jackson, and Linder, 1953). Eight other patients with massive resections showed no neurological abnormalities (Althausen, Doig, Uyeyama, and Weiden, 1950;Berman, Habegger, and Billings, 1953;Fletcher, Henley, Sammons, and Squire, 1960;Holman, 1944;Martin, Robertson, and Dennis, 1948;Mayer and Criep, 1949;Pincus, 1951).…”
Section: Case Reportsmentioning
confidence: 99%
“…The steatorrhoea was reduced by a modification of the diet, animal fat being replaced by vegetable fat as olive oil and the fluid intake was restricted, particularly the milk (Clayton and Cotton, 1961). In Case 6 the last 10 cm.…”
Section: Discussionmentioning
confidence: 97%
“…An initial five-day calcium balance (balance study I) as described by Clayton and Cotton (1961) showed definite hypercalcuria ( Fig. 1 and Table 3).…”
Section: Investigations and Resmentioning
confidence: 94%